Distribution and Conservation Status of Phlegmariurus (Lycopodiaceae) in the State of Veracruz, Mexico. (March 2015) - Armenta-Montero, Samaria; Carvajal-Hernández, César I.; Ellis, Edward A.; Krömer, Thorsten
The fern and lycophyte flora of Mexico contains 13 species in the genus Phlegmariurus (Lycopodiaceae; club moss family), of which nine are found in the state of Veracruz ( P. cuernavacensis, P. dichotomus, P. linifolius, P. myrsinites, P. orizabae, P. pithyoides, P. pringlei, P. reflexus, P. taxifolius ). They are located primarily in undisturbed areas of humid montane, pine-oak and tropical humid forests, which are all ecosystems threatened by deforestation and fragmentation. The objective of this study was to evaluate and understand the distribution and conservation status of species of this genus in the state of Veracruz, Mexico. Using Maxent, probability distributions were modeled based on 173 herbarium specimens (25% from recent collections by the authors and/or collaborators), considering factors such as climate, elevation and vegetation cover. Additionally, anthropogenic impacts on the original habitat of each species were analyzed in order to assign threatened categories based on IUCN classifications at regional levels. Results show that potential distributions are located in the montane regions of the central and southern parts of the state. All nine Phlegmariurus species in Veracruz were found to be in some category of risk, with P. orizabae classified as critically endangered, having only a single specimen collected in 1854. The main reasons for species threats are the continuous loss and fragmentation of their natural habitat, uncontrolled harvesting activities, and the lack of protected areas that include humid montane and pine-oak forests in the central region of the state.